Transient Analysis of the Fuzzy Logic-based Speed Control of a Three-phase BLDC Motor - Raja, S.; Rathinakumar, M. (Engineering, Technology & Applied Science Research, 2023)
The energy-efficient motor is a vital requirement for modern industrial, automobile, and home appliance drives. Among the special machines, the Brushless DC Motors (BLDCMs) are more attractive to the application engineer because they offer high power-to-weight ratio, compact construction, do not require consistent maintenance, and have an efficiency margin of 85–90%. This study uses FPGA to create fuzzy logic-based speed control for a three-phase BLDCM with transient time domain characteristics. The fuzzy logic-based controller algorithm is implemented using the FPGA Xilinx Spartan board, which receives the actual speed from a position sensor located inside the BLDCM. It calculates the ratio of the duty cycle of the Pulse Width Modulation (PWM) pulse. It is triggered by the driver system of the BLDCM drive to attain the reference speed. The performance characteristics of a BLDC motor drive such as steady-state error, peak overshoot, speed drop under loaded conditions, and restoration time after loaded conditions were analyzed using MATLAB/Simulink 2014. The hardware configuration setup is validated by the suggested system’s simulation response.